Outcomes of Patients with Glanular Hypospadias or Dorsal Hood Deformity with Mild Chordee Ttreated by Modified Firlit’s Technique - Alizadeh, Farshid; Shirani, Shekoufeh (Urology Journal, 2016)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:Cambria; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> <!–StartFragment–> Purpose: To assess the success and complication rates of glanular hypospadias or dorsal hood deformity surgery,using a modified Firlit’s technique without glanuloplasty. Materials and Methods: Between May 2013 and December 2015, 41 patients with glanular hypospadias or dorsalhood deformity without hypospadias and mild ventral chordee underwent surgery. Thirty-eight who completedthe 1 week and 6-month follow-up were retrospectively evaluated. Exclusion criteria were complete absence ofcorpus spongiosum resulting in very thin distal urethra, moderate to severe ventral chordee or deep urethral platethat seemed to be better served by tubularization techniques. Modified Firlit’s technique (a submeatal inverted Vincision in addition to the classic technique) was applied to all patients. Results: The mean age was 20.4±13 months (range: 6-52 months). The only complication was a narrow-bandventral skin necrosis in 1 patient (2.6%) that was replaced by new skin growth without need for further intervention.No other complications including unresolved chordee, urethrocutaneous fistula, meatal stenosis, hematoma,infection or post-operative bleeding was observed. Defining the satisfactory result as the glanular position of themeatus and the absence of residual chordee, all patients had satisfactory outcome. Conclusion: Modified Firlit’s technique is a simple method with excellent cosmetic results and low complicationrate that avoids unnecessary glans dissections. When prepucioplasty is not desired, this technique can be consideredas a viable option. <!–EndFragment–>